Black empowerment and Afro-American values in Toni Morrison’s The Bluest Eye - Karim, Sajjadul; Idrus, Mohd Muzhafar Bin (IIUC Studies, 2020)
The Bluest Eye of Toni Morrison is extraordinarily significant, as it addresses the different sides of American literature, and the lives of the Afro-American people. Although the conventional theological aspects of white culture can negatively influence other characters of Morrison, it is Pecola whose life appears to be increasingly defenseless against the impulses of the individuals who have accepted the Western custom. In a democratic country, people generally have the same value, but there are still prejudices in the concepts of beauty and worthiness. The search for freedom, black identity, the nature of evil and the robust voices of African-Americans have become themes for African-American literature. Folklore covers the history of black and white interaction in the United States and also summarizes the feelings expressed in protest literature1. Morrison argues that the survival of the dark ladies in a white dominated society depends on loving their own way of life and dark race and rejecting the models of white culture or white excellence. This article attempts to examine The Bluest Eye from the perspective of empowerment of blacks and African American and their value system. IIUC Studies Vol.16, December 2019: 111-121